USING WORD WALL TO IMPROVE EFL STUDENTS' VOCABULARY ACHIEVEMENT AT JUNIOR HIGH SCHOOL - Sari, Putri Sindy Arlinsa (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2024)
One component of learning English is vocabulary mastery. Teachers can develop lessons to increase student's vocabulary achievement by using media that is interesting and fun such as Word Wall. The aim of the research was to improve the students’ vocabulary achievement using Word Wall. The setting of this research was at one of secondary school in Banyuwangi, East Java, Indonesia. The present study applied Classroom Action Research (CAR). The data were collected from the vocabulary test and observation. The previous students’ vocabulary mean score was 60. The result from vocabulary test after the action showed that the mean score was 76.2. The result showed that there were significant improvement on students’ vocabulary achievement compared to the students’ vocabulary mean score before using Wordwall media. The result of observation checklist also showed significant improvement from meeting to meeting. In meeting 1, 45.5% actively participated during the teaching and learning process. In meeting, 2, 55% of students participated actively. In meeting 3 and 4, the percentage of students who actively participated in wordwall based vocabulary teaching and learning improved from 60.8% to 90%. The findings suggest that the use of Word Wall as media can significantly improve EFL students’ vocabulary achievement.